Influência do estresse nutricional e do marcador molecular BMS3004 na indução da ovulação pós-parto em vacas de corte - Bastos, Guilherme de Medeiros (2002)
The objective of the first experiment was to compare the efficiency of a hormonal protocol, associated to the temporary weaning for 96 hours, with the definitive weaning at 60 days for induction of estrus and ovulation, considering a molecular marker BMS3004. There were used 181 suckled beef cows, from Charolais (C) and Nellore (N) breeds and their crosses. These cows were genotyped as homozygous (HOM) and heterozigous (HET) for the microsatellite BMS3004, which is localized in the same chromosome that expresses the LH  chain gene. In the day 0 (between 60 and 80 days postpartum), the cows were distributed in two groups. In the hormonal induction group (HI), the cows (n=87) received an intravaginal device (IVD), containing 250mg of medroxiprogesteron acetate (MAP). On day 1, it was injected, intramuscularly (im), 2.5mg of estradiol benzoate (EB) and, on day 7, 500UI (im) of equine chorionic gonadotrophin (eCG). On day 8, the IVD were withdrawn and the calves were weaned for 96 hours. On day 8, the cows (n=96) of the other group were only submitted to early definitive weaning (group EW). Twelve hours after weaning, artificial insemination (AI) was done during four days. After this period, they were mated. The cows of HI group were definitively weaned 26 days after the AI period. The first diagnosis of pregnancy (DP) was done 60 days after the AI period and, the second, 60 days after the end of mating. At day 0, the cows presented body condition (BC) between 2.0 and 3.5 (scale from 1 to 5) and body index (BI) from 47 to 73. The estrus rate was higher in cows from HI group than in those of EW group. The cows with BC 2.5 and 3.0 presented lower (P<0.05) pregnancy rates at 1st DP in the HI group (29.6% and 46.4%) than in the EW group (56.0% and 72.2%). The rates of pregnancy in cows with BI 65-73 did not differ (P>0.05) between the HI and EW groups. The N cows of HI group presented lower (P<0.05) pregnancy rate at 1st DP than the ½ blood (27.7% vs. 64.2%), but they were not different (P>0.05) than the C breed (40.0%). In the HI group, the pregnancy rate at 2nd DP was lower (P<0.05) in HOM cows than HET ones. In this experiment, the early definitive weaning was more efficient than the hormonal induction to improve pregnancy rate. Based in these results, another experiment was designed to develop and evaluate a protocol for inducing ovulation and inseminating suckled beef cows under nutritional stress. A total of 137 cows, between 60 and 75 days postpartum (day 0), were classified according to their BC and distributed in two groups. In the hormonal induction group (HI), the cows (n=71) received an IVD with 250mg of MAP and 2.5mg of EB (im). On day 6, a dose of 500IU of eCG was injected (im) and the calves were temporarily weaned for 96 hours. On the following day (day 7), the IVD were removed. The cows were inseminated 12 hours after estrus detection until 45 hours after removing the IVD. In the cows that did not show estrus during this period, it was injected (im) 100g of GnRH and fixed time AI was done from 16 to 18 hours. In the control group (C), the cows (n=66) had only theirs calves weaned at day 6 for 96 hours. The diagnosis of pregnancy was performed in a mean of 54 days after the AI period. On day 0, all the cows were under nutritional stress (BC from 2.0 to 3.0). In the HI group, the estrus and pregnancy rate of the cows with BC 2.0 (respectively 20.0% and 30.0%) was lower (P<0.05) than those with BC 3.0 (50.0% and 66.6%), but did not differ (P>0.05) from BC 2.5 (23.3% and 47.6%). In the C group, just 2 out of 64 cows showed estrus and were inseminated, but did not result in pregnancy. These results show that the hormonal induction of ovulation, associated to temporary weaning for 96 hours, improves the pregnancy rate in beef cows under nutritional stress between 60 and 75 days postpartum, allowing a three-days period of AI.